Experimental assessment on the performance of hot wire anemometry in and around a permeable medium by comparison with Particle Image Velocimetry - Silin, Nicolas (2021)
The air flow through a test section partially obstructed by a permeable array of wires was measured simultaneously by Hot Wire Anemometry (HWA) and Particle Image Velocimetry. The objective ofthe study was the assessment of the suitability of HWA for the measurement of flow velocities amid and adjacent to groups of small obstacles. In the present case the obstacles are set in a regular array configuring a highly permeable structure. The probe was placed at three characteristic positions: in the free flow close to the wire array, inside the permeable medium, and at the interface between the permeable structure and the free flow. The measurements were performed with the hot wire operating under natural convection and mixed convection heat transfer, and operating the hot wire at different overheat ratios. Natural convection plumes extending over several permeable volume elements were detected when the hot wire was under natural convection, in some cases reaching velocities up to 60 mm/s downstream from the hot wire position. For low velocity flows, natural convection can be regarded as a flow velocity offset, which becomes negligible at local velocities higher than 0.03 m/s. For higher velocities, in the mixed convection regime, the intrusivity of the HWA probe becomes relevant. Furthermore, the flow in the test section used in the study presents a linear instability that produces velocity fluctuations. Availing ourselves of this phenomenon we verified the dynamic response of the HWA at the lowest velocity where the flow shows periodic fluctuations; for a local mean velocity of (0.131 ± 0.012) m/s the HWA showed a satisfactory dynamic response up to 20 Hz.